Analysis of extreme rainfall and landslides in the metropolitan region of the Paraiba do Sul River Valley and North Coast of Sao Paulo, Brazil - da Silva, Rodrigo Cesar [UNESP]; Marengo, José Antônio; Ruv Lemes, Murilo (Springer Nature, 2024)
The impact of hydrological and geological disasters has resulted in significant social, economic, and human losses, which added climate change impacts, and such events have become more frequent and intense. Therefore, our objective is to analyze the extreme rainfall (trends) in the Metropolitan Region of the Paraiba do Sul Valley and North Coast of Sao Paulo (RMVPLN). This analysis will support the most affected areas by landslides identification, which mainly impact roads and their population. In addition, evaluate the atmosphere conditions that supported these extreme rainfall events. To achieve our objectives, we have surveyed historical landslide data reported by the Brazilian government and information related by press and media. The precipitation evaluation used CHIRPS v.2 data and ETCCDI indices and the vertically integrated moisture flow and wind speed were calculated by ERA5 reanalysis. Our results show that the frequency and intensity of rainfall indicators such as seasonal PRCPTOT, R20mm, R30mm, and SDII have increased, particularly in the coastal and mountainous regions of São Paulo. This is due to positive anomalies of moisture transport and an increase of ocean winds influenced by the intense South Atlantic Subtropical Anticyclone (SASA). The region with the highest susceptibility to landslides triggered by extreme rainfall is the one that combines deforested areas, high slope topography, and excessive anthropic intervention. The presence of mountainous regions increases the risk of landslides, which can damage local infrastructure and expose the vulnerability of populations in these risk areas.